Development and validation of a monitoring instrument for sport psychology practice: The Sport Psychology Outcomes and Research Tool (SPORT) - Hansen, A. A.; Perry, J. E. (Journal of Clinical Sport Psychology, 2019)
Evidence for the mechanisms of change by which sport psychology interventions enhance performance is limited and treatment monitoring and outcomes measures would assist in establishing evidence-based practices. The present paper fills a gap in sport psychology literature by demonstrating the development and validation of a new measure (Sport Psychology Outcomes and Research Tool; SPORT). Study 1 described test construction and pilot item selection with 73 collegiate student-athletes. Twenty-three pilot items contributed unique variance while maintaining the original constructs and were selected from 80 initial items. In Study 2, exploratory and confirmatory factor analyses were conducted with collegiate student-athletes (n = 220), revealing a 17-item, four-factor model measuring Athlete Wellbeing, Self-Regulation, Performance Satisfaction, and Sport-Related Distress. Concurrent validity was supported through correlational analyses. Overall, results supported the SPORT as a new transtheoretical tool for monitoring effectiveness and outcomes of sport psychology interventions.